How Rural Students Accomplish Online Learning During Pandemic: A Study from Elementary School in Indonesia - Wulandari, Medita Ayu; Pratikno, Ahmad Sudi; Senen, Anwar; Nurfurqon, Faridillah Fahmi (Universitas Pahlawan Tuanku Tambusai, 2022)
The Covid-19 pandemic has impacted all areas of life. Based on government restrictions, all educational institutions have implemented online learning. This study investigates elementary students' online learning experiences in rural areas. It refers to the data collected about: students learning motivation, students learning requirements and students' social skills. Data was collected through an online survey. Data were analyzed through three stages of Miles & Huberman, namely data reduction, data presentation, and conclusion drawing. The results showed that during the Covid-19 pandemic, online learning was less effective for elementary students in rural areas. The value of this study is for comprehending what factors support and interfere with the learning satisfaction of elementary students in rural areas related to online learning during the Covid-19 pandemic.